Reliability challenges in 3D IC packaging technology - Tu, K.N. (Microelectronics and reliability, 2011)
At the moment, a major paradigm change, from 2D IC to 3D IC, is occurring in microelectronic industry. Joule heating is serious in 3D IC, and vertical interconnect is the critical element to be developed. Also reliability concerns will be extremely important. For example, in order to remove heat, a temperature gradient must exist in the packaging. If we assume just a difference of 1 °C across a micro-bump of 10 μm in diameter, the temperature gradient is 1000 °C/cm which cannot be ignored due to thermomigration. Equally challenging reliability issues are electromigration and stress-migration. Since the 3D IC structure is new, the details of reliability problems are mostly unknown. This paper presents a projection of the reliability challenges in 3D IC packaging technology on the basis of what we have known from flip chip technology.